No Significant Effects of Smoking or Alcohol Consumption on Risk of Barrett’s Esophagus - Thrift, Aaron P. (2013)
BACKGROUND: Smoking, but not higher alcohol consumption, is associated with increased risk of esophageal adenocarcinoma (EAC) and progression from Barrett’s esophagus (BE) to EAC. However, it is still unclear whether smoking or alcohol is implicated in the development of BE. AIM: To evaluate the associations between smoking, alcohol and the risk of BE. METHODS: The study included eligible patients scheduled for elective esophagogastroduodenoscopy (EGD) and a sample of patients eligible for screening colonoscopy recruited from primary care clinics. We compared 258 patients with definitive BE with two separate control groups: 453 patients from the primary care group (“colonoscopy controls”) and 1,145 patients from the elective EGD group (“endoscopy controls”) with no endoscopic or histopathologic BE. We calculated odds ratios (OR) and 95 % confidence intervals (95 % CI) using multivariable logistic regression models. RESULTS: Seventy-seven percent of BE cases, 75 % of colonoscopy controls and 72 % of endoscopy controls were ever smokers. Of these, approximately 45 % were current smokers. Overall, 91 % of study participants were ex or current alcohol drinkers, with the majority drinking beer. We found no association between various measure of smoking exposure (status, intensity, age at initiation, duration, pack-years and cessation) and risk of BE. Alcohol consumption was not associated with increased risk of BE. Conversely, moderate intake was associated with lower risk (14 to<28 drinks/week, OR 0.39, 95 % CI 0.15–1.00). CONCLUSION: Smoking and alcohol were not strong or consistent risk factors for BE. The likely role of smoking in increasing risk of EAC is through promoting progression from BE to cancer.